PENGARUH PENURUNAN DEBIT AIR SUNGAI KAMPAR TERHADAP KUALITAS AIR DAN PRODUKTIVITAS USAHA KERAMBA IKAN DESA PULAU LAWAS - Harmi Yelmi; Ardiansyah Hamid (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to analyze the effect of decreasing water flow in the Kampar River on fish productivity and income from fish cage cultivation in Pulau Lawas Village. This study used a mixed methods research method combining qualitative and quantitative analysis. Water quality analysis showed a pH of 7.35, a temperature of 38.5°C, dissolved oxygen (DO) of 4 mg/L, and a depth of 2.5 m, which generally still supports fish cultivation activities, despite the relatively high temperature and DO approaching the minimum tolerance limit for fish. Cultivation activities have been ongoing for five years with seven active fish cages, a stocking density of 15,000 per cage, and a six-month maintenance period. The harvest under the current conditions of decreased river water flow is approximately 8,000 fish, with a total weight of approximately 1 ton per cage, resulting in a survival rate (SR) of 53.3%. From an economic perspective, the operational cost of cultivation is Rp24,300,000 per period/cage, and the value of fish sales is Rp28,000,000, resulting in a net profit of around Rp4,000,000 per cage. The interview results show that seasonal changes, both dry and rainy, do not have a significant impact on productivity and business income, so it can be concluded that the decrease in water discharge of the Kampar River has not had a serious impact on the sustainability of fish cage cultivation businesses in Pulau Lawas Village, although water quality management still needs to be improved.